Ієрархічні онтології для автоматизації управління організаційними структурами - Шиян, А. А. (Видавництво Львівської політехніки, 2014)
Описано метод побудови онтологій предметної області, навантажених ціллю діяльності, які придатні для автоматизації управління у виробничих та організаційних структурах. Описано загальні методи побудови ієрархічних онтологій предметних областей. Наведено приклади застосування таких методів. The paper describes the method for construction of ontologies for subject area, which has a purpose for activity. The method is based on two ontologies comparison: one before and one after doing the activity. The hierarchy means that the classes of lower level ontology are the objects for the considered ontology. The hierarchical ontology can be constructed by two ways: one as integration of several ontologies into unified ontology, and another one as deepening the notion’s sense in the present ontology. Three examples for the obtained results are illustrated. These ontologies can be used for automation of industrial and organizational structures.
Keywords: онтологія; ієрархія; ціль; діяльність; автоматизація; ontology; hierarchy; purpose; activity; automation